Partnership Between Government And Private Vocational School In Public Services (Study At The Village Fishermen Filling Station Sumber Jaya Sub-District Of Kampung Melayu City Of Bengkulu) - Novliza Eka Patrisia; Rekho Adriadi (Indonesian Association for Public Administration (IAPA), 2018)
Partnerships between Government and the Private Sector in Public Services. Quality of public services will result in a positive response from the public so it needs a specific strategy in its implementation, one of which is by using Public Private Partnership (PPP). This study aims to describe and analyze the partnership that exists between the government and the private sector, describe and analyze the public response to the quality of service as well as explain the enabling and inhibiting factors in the implementation of public service in Fuel Filling Station of Fishermen (SPBN) Kampung Bahari, of Bengkulu city. The method used in this study used a qualitative approach. Quality of public services in SPBN Kampung Bahari get an appraisal